The Correlation of Vocabulary Mastery and Narrative Text Writing Skills in Perspective of Educational Theory - Soraya, Kety; Hidayat, Sholeh; Anriani, Nurul (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study investigates the correlation between students’ vocabulary mastery and their writing ability in narrative texts at the tenth grade of Vocational Senior High School 8 Kota Serang. Employing a quantitative correlational design, data were collected from 35 students selected through simple random sampling. Two instruments were used: a vocabulary test and a writing test focusing on narrative composition. The validity and reliability of both instruments were confirmed through Pearson Product–Moment and Cronbach’s Alpha analyses. Descriptive statistics showed that the mean score of vocabulary mastery was 75.60 and writing ability was 74.20, both categorized as good. The Pearson correlation analysis revealed a strong and significant positive relationship between vocabulary mastery and writing ability (r = 0.713, p < 0.05), with vocabulary contributing 50.8% to the variance in writing performance. These results support cognitive–constructivist theories proposed by Piaget and Vygotsky, emphasizing that vocabulary development and writing competence evolve through active learning and social interaction. The findings suggest that integrating contextualized vocabulary instruction into writing practice can effectively enhance students’ writing proficiency, especially in vocational education contexts.